Durability of Biodegradable Polymers for the Conservation of Cultural Heritage - Mistretta, Maria C.; La Mantia, Francesco P.; Titone, Vincenzo; Megna, Bartolomeo; Botta, Luigi; Morreale, Marco (Frontiers in Materials, 2019)
The use of polymers for conservation of cultural heritage is related to the possibility to slow down or stop natural deterioration which, in many cases, corresponds to stopping the entrance of liquid water and to favour spontaneous water vapour removal. Unfortunately, hydrophobicity is generally favoured by surface roughness and thus competitive with transparency. It is therefore important to find an optimal balance hydrophobicity, transparency and durability (especially to photooxidation). However, polymers typically used for applications in this field come from non-renewable resources and are not biodegradable. In this work, the mechanical, structural and optical properties of PLA, PBAT and a PBAT/PLA blends, as well as surface properties and water vapour permeability, were investigated before and after exposure to UV irradiation, in order to evaluate their durability and suitability for conservation of cultural heritage.